Influence of Spray Rate on Structural and Optical Properties of Sprayed ZnO Films - Anh, Luu Thi Lan; Bac, Luong Huu; Hung, Pham Phi; Hieu, Nguyen Duc; Neto, Mateus Manuel; Son, Vo Thach; Thai, Tran Thanh (Communications in Physics, 2014)
In this report, the ZnO nanostructure films have been deposited by ultrasonic spray pyrolysis technique (USP) on fluorine doped tinoxide~(FTO) substrate using zinc acetate and aqueous 2-propanol as reactants. The effects of solution spray rate on structural, morphological and optical properties of ZnO nanostructure films were investigated by X-ray diffraction (XRD), atomic force microscopy (AFM) and UV-Vis measurements. ZnO films were crystallized in the hexagonal wurtzite phase and preferential orientation changed with changing of spray rate. Grain size and roughness of films depended on spray rate. Increasing spray rate made the films grown with bigger grain size and higher roughness. Band gap energy was determined from the UV-Vis. Its value was found to be of 3.25 eV and was almost independent on the spray rate.